Epidemiology of basal cell carcinomas treated in public health services (Research, Society and Development, 2025)
Basal cell carcinoma (BCC) is the most common malignant skin neoplasm, accounting for about 75% of non-melanoma skin cancers. It is mainly associated with chronic exposure to ultraviolet radiation, in addition to factors such as skin type, age, and occupation. Objective: To analyze the epidemiological profile of patients with a confirmed diagnosis of BCC in 2024 and 2025. Methodology: An epidemiological, observational, cross-sectional, and descriptive study was conducted, with data collected from medical records and biopsy reports. Sociodemographic and clinical variables and risk factors were evaluated using SPSS (25.0) software. The research was approved by the Ethics Committee of the University of Paraná (CAAE: 92703325.6.0000.0109). Results: A total of 147 patients treated in Francisco Beltrão-PR between 2024 and 2025 were analyzed. Basal cell carcinoma was the most prevalent type (70.1%), followed by squamous cell carcinoma (18.4%), melanoma (1.4%), and others (10.1%). There was a balanced distribution between genders (51% male and 49% female), a predominance of white individuals (92.5%), and a higher incidence in the 61-75 age group (44.9%). The face was the most affected anatomical site (54.4%). No statistically significant associations were identified between clinical variables and histological type (p > 0.05). Conclusion: The findings are in line with national trends, reinforcing the need for regional prevention strategies, educational actions on photoprotection, and expansion of early detection, especially in primary care.